(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
An efficient method of asymmetric stoichiometric synthesis of s-t-butyl-D-cysteine via addition of t-(CH3)CSH to the double C=C bond of dehydroalanine in its chiral Ni2+ complex of Schiffs base with the chiral auxiliary D-2-N-(N’-benzylprolyl)aminobenzophenone was elaborated. The optical active amino acid s-t-butyl-D-cysteine with high optical purity (e.e. > 98%) was separated after decomposition of the reaction mixture by HCl. The stereoselectivity of nucleophilic addition amounts 92%.